Profiles by Sex of Brain MRI and Cognitive Function in The Framingham Offspring Study - Albert, Mark (2010)
OBJECTIVE: To examine whether there are sex-specific associations between brain MRI measures and neuropsychological test performance. BACKGROUND: Differences in cardiovascular risk factors (CVRF) have been linked to decreased total cerebral brain volume (TCBV) and white matter hyperintensities (WMH). Although brain morphology has been related to cognitive performance, few studies have addressed sex-specific effects in this relationship. METHODS: Framingham Offspring who were stroke and dementia-free underwent a brain MRI scan and neuropsychological (NP) testing (n=2,085; 978 men). Factor analysis identified four domain-specific neuropsychological factors. MRI participants were divided into four MRI subgroups based on measures of TCBV and combinations of the presence of WMH and silent cerebral infarcts (≥3mm; SCI). RESULTS: Overall, the relationship between MRI and NP measures was similar between the sexes. The exception was that only men showed a positive relationship between executive function (EF) and cerebrovascular disease defined as large white matter hyperintensity volume plus SCI. This finding was attributed only among men with FSRP scores > 90(th) percentile range (p=0.0019). CONCLUSIONS: Measures of brain atrophy and subclinical markers of vascular disease showed that sex does not significantly alter the relationship between MRI and NP, except among men and women who are at high risk for stroke; these men show poorer performance on EF, whereas the women do not.